Pelvic cellulitis caused by Raoultella planticola in a neutropenic patient. Issue 4 (April 2019) - Al-Sawaf, O.; Garcia-Borrega, J.; Vehreschild, J.J.; Thelen, P.; Fätkenheuer, G.; Shimabukuro-Vornhagen, A.; Kochanek, M.; Böll, B.
Abstract: Raoultella planticola is a gram-negative, encapsulated, aerobic bacterium within the Enterobacteriaceae family. It has been primarily described as pathogen in cases with pneumonia and gastrointestinal infections. Here we describe a case of severe pelvic cellulitis in a patient with neutropenia following induction therapy for myeloid sarcoma. The patient experienced a septic shock and was treated successfully with antibiotic therapy. A literature review is provided to put this case in context with previous reports on R. planticola . This report highlights that awareness for uncommon pathogens is crucial in the clinical management of infections in neutropenic patients.